ESSENCE AND CONTENT OF TEACHER TRAINING INSTITUTIONS COMPLETE GENERAL AVERAGE EDUCATION UNDER THE CONDITIONS OF A MASTER’S DEGREE - Yakubovska, Svitlana; Oleksin, Yurii; Kochubey, Alla; Plyuta, Natalia; Tsetsyk, Yaroslav (European Science, 2024)
The contextual analysis of the main domestic and European normative legal documents that regulate the functioning and development of education, terminological dictionaries allowed to identify a group of the most used terms that reveal the peculiarities of